Tyranny of distance: Home advantage and travel in international cllub football - Goumas, C. (International Journal of Performance Analysis in Sport, 2014)
Home advantage (HA) is well documented in a wide range of team sports including association football (soccer). Adverse effects of travel appear to play a role, although it is unclear which aspects of travel are important. Match data from major international club football competitions in four confederations of the International Federation of Association Football (FIFA) were used to investigate the roles distance travelled and crossing time zones play in HA, and how their effects may vary worldwide. Poisson regression analysis was used to estimate the effect of each of these travel factors on HA. There was no evidence of an effect of away-team travel on HA in Asia. There was, however, a significant positive association between HA and distance travelled in Africa (p<0.01) and Europe (p<0.05). HA increased significantly (p<0.001) with increasing number of time zones crossed by away teams in South America, but there was no evidence of such an effect in the other continents investigated. The results show that both absolute distance travelled by away teams and the number of time zones crossed can be associated with poorer match performance, although their effects appear to vary considerably between continents.